2003
DOI: 10.1117/12.517247
|View full text |Cite
|
Sign up to set email alerts
|

<title>The 1x384 hybrid linear infrared focal plane arrays on InAs MOS structure for spectrometric applications</title>

Abstract: Technology and design of linear lx3 84 MIS photodetectors on InAs homoepitaxial substrate are developed. The experimental results on JR focal plane arrays (JR FPA) intended for rapid JR spectrometers with registration time 0,1 -50 ms are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Previously, we realized the fluorinated anodic layer (FAL)/InAs interface with minimum D it ∼ (2-5) × 10 10 eV –1 cm –2 at 77 K by anodic oxidation in liquid and dry fluorine-containing mediums. A medical-cooled CID camera based on In 2 O 3 /SiO 2 /FAL/InAs MIS structures with high-contrast images of two-dimensional thermal patterns with a resolution up to 7 mK was fabricated. , The sharp influence of fluorine on the D it of the AL/InAs interface was established . The FAL chemical composition, the morphology of the InAs surface and FAL/InAs interface, as well as electrophysical parameters of Au/FAL/InAs metal-oxide–semiconductor (MOS) structures were studied. The D it and the composition of FAL dependences on fluorine concentration were revealed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we realized the fluorinated anodic layer (FAL)/InAs interface with minimum D it ∼ (2-5) × 10 10 eV –1 cm –2 at 77 K by anodic oxidation in liquid and dry fluorine-containing mediums. A medical-cooled CID camera based on In 2 O 3 /SiO 2 /FAL/InAs MIS structures with high-contrast images of two-dimensional thermal patterns with a resolution up to 7 mK was fabricated. , The sharp influence of fluorine on the D it of the AL/InAs interface was established . The FAL chemical composition, the morphology of the InAs surface and FAL/InAs interface, as well as electrophysical parameters of Au/FAL/InAs metal-oxide–semiconductor (MOS) structures were studied. The D it and the composition of FAL dependences on fluorine concentration were revealed.…”
Section: Introductionmentioning
confidence: 99%
“…A medical-cooled CID camera based on In 2 O 3 /SiO 2 / FAL/InAs MIS structures with high-contrast images of twodimensional thermal patterns with a resolution up to 7 mK was fabricated. 7,8 The sharp influence of fluorine on the D it of the AL/InAs interface was established. 9 The FAL chemical composition, the morphology of the InAs surface and FAL/ InAs interface, as well as electrophysical parameters of Au/ FAL/InAs metal-oxide−semiconductor (MOS) structures were studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Controlled growth of fluorine-containing anodic oxide layers (FAOL) in different liquid and gas media is one of the ways to modify a semiconductor surface to create metal–insulator–semiconductor (MIS) structures. For InAs, the method provides low DOS (<5 × 10 10 eV –1 cm –2 at 77 K) in Au/FAOL/InAs(111)­A and In 2 O 3 /SiO 2 /FAOL/InAs­(111)­A MIS structures. For GaAs, plasmochemical oxidation of the semiconductor surface in oxygen and CF 4 medium reduces the DOS at the FAOL/GaAs interface 50 times (to a level ∼5 × 10 11 eV –1 cm –2 at 300 K) compared to the anodic oxide layers (AOL)/GaAs interface formed without fluorine . The FAOL composition analysis by the X-ray photoelectron spectroscopy method shows that the transition region at the FAOL/A III B V interface consists of fluorides and oxyfluorides of semiconductor elements, and its formation can explain an elimination of interface states in the band gap.…”
Section: Introductionmentioning
confidence: 99%
“…For InAs, the method provides low DOS (<5 × 10 10 eV –1 cm –2 at 77 K) in Au/FAOL/InAs(111)­A and In 2 O 3 /SiO 2 /FAOL/InAs­(111)­A MIS structures. For GaAs, plasmochemical oxidation of the semiconductor surface in oxygen and CF 4 medium reduces the DOS at the FAOL/GaAs interface 50 times (to a level ∼5 × 10 11 eV –1 cm –2 at 300 K) compared to the anodic oxide layers (AOL)/GaAs interface formed without fluorine . The FAOL composition analysis by the X-ray photoelectron spectroscopy method shows that the transition region at the FAOL/A III B V interface consists of fluorides and oxyfluorides of semiconductor elements, and its formation can explain an elimination of interface states in the band gap. Note that the complex composition of the AOL/In­(Ga)­As interface transition region considerably complicates finding out the microscopic nature of interface states.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of works [7,8] and references therein, it was shown that the fluorination of GaAs, InAs, and other A III B V semiconductor surfaces leads to a significant decrease in the DSS. It was found in [9][10][11][12][13][14] that an intermediate fluorine-containing anodic oxide layer is formed at the oxide-semiconductor interface, which contributes to a decrease in the density of surface states. Moreover, it was shown that the formed oxide layers on the semiconductor surface contain Group III element fluorides and Group V element oxyfluorides.…”
Section: Introductionmentioning
confidence: 99%